Fission and properties of neutron-rich nuclei : (World scientific, 2003)
The explosion of new data on fission processes & properties of neutron-rich nuclei made possible by new detection & accelerator facilities called forth an international conference to highlight the latest results & future directions in this rapidly developing field. Conference held November 1015, 1997 at Sanibel Island, Florida, U.S.A. --This text refers to an out of print or unavailable edition of this title.